Temperature Characteristic of Yaw Damper and Its Effect on Vehicle Stability - GAO Hongxing; XU Tengyang; CHI Maoru; WU Xingwen; GUO Zhaotuan (机车电传动)
The field test and simulation analysis were accomplished to analyze the impact of oil temperature on inherent dynamic performance of yaw damper and vehicle stability and temperature characteristic of yaw damper. The test results showed that the absorbed energy by yaw damper, the dynamic damping and stiffness of damper increased with the temperature decreasing in the proper range of oil temperature, while decreased with the temperature decreasing when it exceeded the proper range of oil temperature; The temperature and dynamic feature had no obvious change and yaw damper could not recover normal state within two hours as yaw damper’s oil temperature was not at the range of normal working temperature. The simulation results also showed that the critical hunting speed increased with the temperature decreasing in the proper range of oil temperature, while decreased with the temperature decreasing when it exceeded the proper range of oil temperature.